The story of the merger of Siri Satguru Nanak Dev Ji Maharaj with the divine eternal light, and also Bara maha (programme for twelve months), composed by the Satguru one day before the event - Doabia, H. S., 1907- (Harbans Singh Doabia Satwant Kaur Charitable Trust, 1973)
On the death of Nanak, 1469-1538, 1st guru of the Sikhs.